Examining the role of green human resources management (GHRM) in building green corporate image and green competitive advantage in malaysian public universities - Mimi Rabita, Abdul Wahit (2022)
The Sustainable Development Goals (SDG) is the core agenda and most of the organization had a fundamental role. Most of Malaysian universities face immense internal issues increasing becoming greener and more eco-friendly. It is important for the university’s image to support the environment in order to create an environmentally sensitive, resources –efficient and social responsibility in organization. The global rankings of Malaysia universities also struggling to make a dent on the international stage. Its beneficial to organizations in create culture, cost reduction, employee retention, reputation in international ranking and attraction. This study provide valuable insight that how Green Human Resources Management (GHRM) drive and contributes to the green corporate image (GCI) and green competitive advantage (GCA). By applying the theory of Ability –Motivation and Opportunity (AMO) perspective and Resource Based View (RBV) both theory would assess the impact of GHRM practice on environmental performance and competitive advantage in public university. A total of 161 respondent comprising 20 public universities were completed and return representing 53.6% response rate. The Smart PLS 3.3.9, the partial least square structural equation modelling (PLS-SEM) technique was used in the preliminary analysis for data screening of normality, other relevant assumptions and research analysis. Based on the outcome of the data screening, a total of 150 questionnaires were used in the subsequent analysis. With the exceptions of four hypotheses, all the other four hypotheses were supported. The current findings hold significant implications for the theoretical and managerial aspects of GHRM within the context of research and academic institutions in Malaysia. In addition, this study offers several insights to the university initiatives towards green.